L''ékphrasis' oltre l''ékphrasis': due ragionamenti sul saggismo di Roberto Longhi (Mantichora. Italian Journal of Performance Studies, 2020)
The idea of the paper is that Roberto Longhi’s ékphrasis goes beyond the usual limits and forms of this kind of writing, but without altering the statutes and all purposes. This need originates from a basic problem: the unbridgeable gap between image and word that describes it.